Comparison of the protein quality of dietetically treated phenylketonuria patients with the recommendations of the WHO expert consultation - Krauch, Gabriele; Müller, E.; Anninos, Alexandros; Bremer, Hans J. (European journal of pediatrics, 1996)
The protein quality of the diets of phenylketonuria (PKU) children of different ages (3 months, 10 months, 3 years, 8 years, 12 years, 16 years) with low or high phenylalanine (Phe) tolerance was assessed according to the recommendations of the FAO/WHO consultation group [13]. The amount of each essential amino acid (AA) per gram dietary protein was calculated and compared to the reference. The resultant amino acid score (AAS) indicated a limited to inadequate biological protein quality of the diets in 3-month-old infants (2.2 g protein/kg body weight/day) and 10-month-old infants (2.0 g protein/kg body weight/day) with a “high” Phe tolerance. In all other age groups the AAS was >100%. However remarkable imbalances in the AA pattern were apparent. Beginning with the age of 3 years (1.7 g protein/kg body weight/day) the intake of the AA lysine and isoleucine was three or two times higher than recommended. At the age of 8 years (1.4 g protein/kg body weight/day) the intake of three AA (valine, isoleucine, lysine) was — related to the WHO recommendations − 217%, 229% and 291%. Similar results could be found in the age groups of 12 years (1.1 g protein/kg body weight/day) and 16 years (0.9 g protein/kg body weight/day), respectively. These calculations might help to reconsider the composition of the AA mixtures used in the dietetic treatment of PKU patients.
Gesehen am 29.05.2024